Examining the Negative Impact of TikTok Usage on Elementary Students' Learning Motivation: Menelaah Dampak Negatif Penggunaan TikTok terhadap Motivasi Belajar Siswa Sekolah Dasar - Mariyati, Lely Ika; Wilmar, Muhammad Pascal (Indonesian Journal of Education Methods Development, 2024)
This correlational quantitative study investigates the impact of TikTok social media usage intensity on academic learning motivation among elementary school students. Using a sample of 80 students from grades 4, 5, and 6, selected through accidental sampling, the research employed TikTok usage intensity scales and an academic learning motivation scale based on self-determination theory. Data analysis with Pearson correlation in JASP software revealed a significant negative relationship between TikTok usage intensity and students' learning motivation, supporting the hypothesis. Recommendations include implementing social media regulations in educational settings and promoting awareness among students, parents, and educators about the potential adverse effects of excessive TikTok use. Future research could explore this topic further with more sophisticated methodologies to enhance understanding. Highlight: Quantitative approach reveals significant negative correlation. Accidental sampling used for diverse grade representation. Recommendations advocate media regulation for academic focus. Keywoard: TikTok, Elementary students, Learning motivation, Social media impact, Correlational study